Monetary Policy and the Stability of Financial Markets - Zawirski, Jacek (Journal of Finance and Financial Law, 2014)
The article aims to present the interaction between monetary policy, economic conditions and the condition of the financial markets. The last global crisis and subsequent actions of central banks have highlighted how closely they are linked. In the study presented has been the impact of monetary policy on economic trends, real estate market and the trading of financial instruments. The author argues that monetary policy has a growing impact on the economic situation and the behavior of financial markets. The study shows the need for the stability of the financial system for the proper functioning of economies.